A solid Zn complex catalyst for efficient transformation of CO2 to cyclic carbonates at mild conditions. (30th July 2022) - Ge, Yuansheng; Liu, Wei; Zou, Yizhen; Cheng, Guoe; Ke, Hanzhong
Abstract: A solid Zn Complex (Zn(HBA)2 ) with o -Hydroxybenzyl-Amine, which can be easily prepared by a one-step synthesis method, was exploited for the CO2 transformation to cyclic carbonates. The results demonstrated that Zn(HBA)2 is a high-efficiency catalyst in the coupling reaction between CO2 and epoxides under solvent-free conditions. Under mild conditions (80 °C, atmospheric CO2 ), epoxides with different substituents have been successfully transformed into the relevant cyclic carbonates with high yields and selectivity (>99%). The turnover frequency (TOF) was reached to 21, 667 h −1 for the coupling of CO2 and epichlorohydrin (ECH) into chloropropene carbonate (CPC) under 120 °C and a 1.8 MPa of CO2 pressure within 3 h. This catalyst is capable of recovering and reusing by simple filtration. The catalytic mechanism of Zn(HBA)2 for the cycloaddition reaction was proposed. Graphical abstract: A solid Zn Complex acts as heterogeneous catalyst for the coupling of CO2 and epoxides without solvent at mild conditions. The catalyst can be recovered and reused by a simple filtration. Image 1 Highlights: A solid Zn Complex (Zn(HBA)2 ) was synthesized by one-step synthesis method. A series of epoxides have been converted into the corresponding cyclic carbonates in high yields at mild conditions. The TOF of 21, 667 h −1 was achieved for the conversion of CO2 with epichlorohydrin into cyclic carbonate. Zn(HBA)2 can be recovered and reused by a simple filtration without obvious loss of its catalytic activity after five cycles.